2019
DOI: 10.1093/aob/mcz196
|View full text |Cite
|
Sign up to set email alerts
|

Leaf trichomes in Metrosideros polymorpha can contribute to avoiding extra water stress by impeding gall formation

Abstract: Background and Aims Plants inhabiting arid environments tend to have leaf trichomes, but their adaptive significance remains unclear. Leaf trichomes are known to play a role in plant defence against herbivores, including gall makers. Because gall formation can increase water loss partly through increased surface area, we tested the novel hypothesis that leaf trichomes could contribute to avoiding extra water stress by impeding gall formation, which would have adaptive advantages in arid envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The effects of water limitations on the density of leaf trichomes have been widely investigated in previous studies (Kessler et al 2007, Cach-Perez et al 2016, Amada et al 2019, most of which indicated that trichome densities increase under restricted water conditions, as demonstrated by our results (Fig. 3).…”
Section: Effects Of Climatic Factors On Leaf Trichome Density Across ...supporting
confidence: 82%
“…The effects of water limitations on the density of leaf trichomes have been widely investigated in previous studies (Kessler et al 2007, Cach-Perez et al 2016, Amada et al 2019, most of which indicated that trichome densities increase under restricted water conditions, as demonstrated by our results (Fig. 3).…”
Section: Effects Of Climatic Factors On Leaf Trichome Density Across ...supporting
confidence: 82%
“…Mean annual precipitation, mean annual temperature, minimum and maximum temperature, Penman–Montieth-modeled potential evapotranspiration, transpiration, wet canopy evaporation, soil evaporation, and evapotranspiration were calculated for each site [ 67 , 68 ]. An aridity index (AI) was calculated as the mean annual precipitation/potential evapotranspiration to further assess plant community composition sensitivity to dryness following methods detailed in a recent study of Metrosideros leaf trichomes in Hawai’i [ 78 ]. The lower the index, the more arid the conditions: AI < 0.03, hyper-arid zone; 0.03 < AI < 0.20, arid zone; 0.20 < AI < 0.50, semi-arid zone; 0.50 < AI < 0.75, dry, sub-humid zone; AI > 0.75, humid zone [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this difference could not be explained solely by the presence or absence of the trichome layer, as its contribution to this resistance was relatively small (1-9%). A subsequent study (5) showed that insect gall formation significantly altered leaf physiological traits, resulting in increased water loss and decreased leaf trichome density. This finding implies that leaf trichome development of this plant could be plastic in response to environmental cues prompting adjusted functions.…”
Section: Boundary Layer Effectsmentioning
confidence: 98%